OPTIMUM ROUTE EVALUATION OF PERMANENT SETTLEMENTS FOR ACCESSING TO PUBLIC FACILITIES AFTER MERAPI 2010 ERUPTION IN SLEMAN REGENCY - , Alfi Nur Rusydi, Prof. Dr.rer.nat. Junun Sartohadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Permanent settlements were built to accommodate living needs of local people since they lost their settlement caused by Merapi 2010 eruption. The accessibility problems appeared since repairing infrastructures and public facilities after disaster occurred, especially route roads network connected from settlement to given public facilities was still unfinished. Optimum route evaluation was needed to find out which route that could be accessed effectively and be revitalized using model influenced by constraints, such as road length, travel time, route steepness, road quality, and traffic condition. Evaluation was done in several permanent settlements that had accessibility problems such as Batur, Gondang, Singlar, Glagahmalang, Banjarsari, Pagerjurang and Karangkendal. Butuh market and Pakem market were public facilities needed to be accessed by local people living in Batur and in Gondang, whereas Pakem market was needed to be accessed by them living in Pagerjurang and Karangkendal. Local people in Singlar, Banjarsari, and Karangkendal had route problem to access sub district office of Cangkringan. Research was done by road network analysis using Geographic Information System (GIS) and Remote Sensing (RS) completed with interviewing and participation mapping with local people. Research results shown that optimum routes did not mean they being safe from volcanic hazard, although they had shorter road length and travel time, less steep route, better road quality, and quieter traffic. Most optimum routes of Batur, Gondang, Singlar, Banjarsari, and Glagahmalang passing Gendol river were located on the higher hazardous prone area of volcanism event. Therefore, the best optimum route was chosen on the routes that were far from Gendol river which was main channel for pyroclastic flow and lahars. Meanwhile, the best optimum route from Pagerjurang to Pakem market was located on the route which has lighter traffic condition. In weekend, the traffic of those routes would be heavier than on weekday because of holiday. Traffic would also be heavier in the day than in the morning because of rush hours.